Інформаційне суспільство та лабіринти репрезентації - Вишинський, Святослав (Видавництво Львівської політехніки, 2014)
The theses deal with the problems of construction of the network reality and its upcoming challenges. Tendencies for the duplication of reality and for pluralisation of the virtual identities are the same tendencies that threaten mankind with probable loss of personal freedom. As long as modern technologies provide mass communication they deprive of privacy, making every single word, symbol or thought a part of transparent data systems.
Keywords: ідентичність; реальність; віртуальність; комунікація; інформація; постмодерн